Pengembangan E-Modul Interaktif Berbasis Historical Perspective pada Mata Kuliah Jurnalisme Kepariwisataan Sejarah - Matitaputty, Jenny Koce; Ima, Wa; Pessy, Natalya Claire (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to develop teaching materials in the form of e-modules and which are able to improve the historical perspective of students in the historical tourism journalism course. The method used is Research and Development (R&D) with the ADDIE model. The results of the study went through the initial needs analysis stage to analyze the learning needs of study program graduates and course learning outcomes in accordance with the applicable curriculum. At the design stage, the concept and content of the material to be used as an e-module were designed. The study of historical tourism journalism course material is to study historical locations in Maluku. The development stage, realizing the e-module product design developed using the premium Canva application. The implementation stage, after the e-module has been designed, the e-module is tested on instruments both materials and e-module teaching materials and through several revisions to improve the e-module. Furthermore, it is implemented to students of the history education study program who offer MK. Historical tourism journalism. The evaluation stage, the results of the Paired Sample T-Test test obtained based on the pre-test and post test score data with a significance value (2-tailed) of 0.000. So that it can be concluded that there is a difference in learning outcomes before and after treatment with e-modules, meaning that there is a positive influence on the use of e-modules.